Guest

Prove that a.m = g.m=h.m if all the values are equal

Prove that  a.m = g.m=h.m if all the values are equal
 

Grade:12th pass

2 Answers

Saurabh Koranglekar
askIITians Faculty 10336 Points
3 years ago
576-442_1.PNG
Arun
25758 Points
3 years ago
 
 
 
You can proove by assuming both the numbera as x and x.
 
Then
A.M = x +x /2 = 2x/2 = x
 
G.M = sqrt (x²) = x
 
H.M = 2x* x/(x+x) = 2x²/2x = x
 
Hence A.M = G.M = H.M
 
Regards
Arun

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free